1989
DOI: 10.1002/1097-0142(19890115)63:2<243::aid-cncr2820630207>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Mucocutaneous side effects of brequinar sodium. A new inhibitor of pyrimidine de novo biosynthesis

Abstract: Brequinar sodium (NSC 368390; DUP 785) is a new inhibitor of pyrimidine de novo biosynthesis which has completed Phase I clinical trials within the framework of the Early Clinical Trials Group of the European Organization for Research and Treatment of Cancer (EORTC). The main side effects of this compound are myelosuppression, nausea and vomiting, stomatitis and/or mucositis, and skin rash. In this report, the authors describe the pattern of mucocutaneous side effects of Brequinar sodium in patients who receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The second patient experienced a grade 4 rash after the second dose (cumulative dose, 2,400 mg). The rash associated with high-dose intermittent administration of brequinar has been described elsewhere [ 10]. Eight episodes of grade 3 toxicity occurred in five patients.…”
Section: Resultsmentioning
confidence: 93%
“…The second patient experienced a grade 4 rash after the second dose (cumulative dose, 2,400 mg). The rash associated with high-dose intermittent administration of brequinar has been described elsewhere [ 10]. Eight episodes of grade 3 toxicity occurred in five patients.…”
Section: Resultsmentioning
confidence: 93%
“…The inhibitors A77‐1726 and brequinar bind within this channel, athough there is some debate as to whether they bind to precisely the same site 13 . Although brequinar has other significant toxicities such as hematopoetic and skin 14,15 the relative absence of liver toxicity suggests that inhibition of DHO‐DH may not be the mechanism for liver toxicity discussed below, as this was not observed in brequinar‐treated patients. At the doses used clinically for RA, A77‐1726 does not affect the earliest stages of lymphocyte activation, such as transcription of IL‐2 or nuclear factor of T‐cell activation (NFAT) 16 …”
Section: Mode Of Actionmentioning
confidence: 99%
“…A study of Brequinar anti-tumour properties showed that Brequinar inhibited the growth of a broad spectrum of human solid tumours implanted in nude mice [12]. Brequinar sodium is currently in phase 2 clinical trials, however, several complications and toxicities of Brequinar sodium have been reported in Phase 1 clinical trials in patients with solid tumours mainly; myelosupression, thrombocytopenia, nausea, vomiting, skin rashes and mucositis [13]. These side effects are disappointing and this limits its potential use in AML [11].…”
Section: Introductionmentioning
confidence: 99%